2018
DOI: 10.1021/acsmedchemlett.8b00287
|View full text |Cite|
|
Sign up to set email alerts
|

Selective PPARδ Modulators Improve Mitochondrial Function: Potential Treatment for Duchenne Muscular Dystrophy (DMD)

Abstract: The X-ray structure of the previously reported PPARδ modulator bound to the ligand binding domain (LBD) revealed that the amide moiety in exists in the thermodynamically disfavored -amide orientation. Isosteric replacement of the-amide with five-membered heterocycles led to the identification of imidazole (MA-0204), a potent, selective PPARδ modulator with good pharmacokinetic properties. MA-0204 was tested in mice and in patient-derived muscle myoblasts (from Duchenne Muscular Dystrophy (DMD) patients); alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The in vivo study on gene expression data analysis indicated that compound 36 is safer than GW501516. 166 Lagu et al 109 also reported another potent and selective PPARδ agonist, MA-0204 (37) by isosteric replacement of the amide group with an imidazole ring. Furthermore, in vitro and in vivo assays in mice and rats indicated that compound 37 has a favorable pharmacokinetic profile, suggesting that the compound is a potential agent for the treatment of Duchenne muscular dystrophy (DMD).…”
Section: Medicinal Chemistry Of Synthetic Pparδ Agonistsmentioning
confidence: 99%
See 4 more Smart Citations
“…The in vivo study on gene expression data analysis indicated that compound 36 is safer than GW501516. 166 Lagu et al 109 also reported another potent and selective PPARδ agonist, MA-0204 (37) by isosteric replacement of the amide group with an imidazole ring. Furthermore, in vitro and in vivo assays in mice and rats indicated that compound 37 has a favorable pharmacokinetic profile, suggesting that the compound is a potential agent for the treatment of Duchenne muscular dystrophy (DMD).…”
Section: Medicinal Chemistry Of Synthetic Pparδ Agonistsmentioning
confidence: 99%
“…A SAR study revealed the importance of the isosteric replacement of linker (amide group) with imidazole moiety, and replacing the 2-furyl group with 4-trifluoromethoxy group for improved PPARδ selectivity over PPARα and PPARγ. 109 Finally, on the basis of the structure of GW501516 and compound 35, we recently synthesized and detailed an SAR of Y-shaped biaryl analogues and identified the novel compound (38), with a high transactivation activity (PPARδ EC 50 = 2.6 nM) and over 3846-fold selectivity to PPARα and PPARγ. 121 Compound 38 was designed based on the structure of GW501516 by replacing a thiazole group with a phenyl ring (Figure 10B).…”
Section: Medicinal Chemistry Of Synthetic Pparδ Agonistsmentioning
confidence: 99%
See 3 more Smart Citations